PRACTICE OF ECOLOGICAL CITIZENSHIP IN COMMUNITY RIVERBANKS IN WASTE MANAGEMENT BASED ON THE 3R PRINCIPLES IN KAMPUNG BIRU, BANJARMASIN CITY - Siti Ainur Rahmi; Dian Agus Ruchliyadi (GoAcademica Research dan Publishing, 2026)
Ecological citizenship is a form of concern and participation of citizens in protecting the environment to support a sustainable environment. The concept of ecological citizenship can be practiced through proper waste management efforts based on the 3R principle (Reduce, Reuse and Recycle). This principle encourages active community participation in reducing waste generation from households. This study aims to analyze the ecological condition of riverbanks, 3R-based waste management practices, and obstacles in waste management in Kampung Biru. Data collection techniques were carried out through observation, interviews, and documentation, which were then analyzed through data presentation, data reduction, and drawing conclusions. Research results show that the ecological condition of the riverbanks in Kampung Biru indicates pollution, primarily due to waste being thrown into the river. Waste management based on the 3R principle is still at a suboptimal stage. This is evident from the dominance of simple waste separation practices that only distinguish between organic and inorganic waste, without being accompanied by significant reduction efforts. The Reuse practice is seen in some residents who repurpose used items into plant pots. Meanwhile, the Recycle practice is carried out indirectly by some residents by collecting used goods and plastic waste to sell to scrap collectors. Obstacles in waste management in Kampung Biru include internal obstacles such as the habits of some residents who still throw garbage into the river and the perception that waste management is a complicated activity, while external obstacles are indicated by the lack of facilities such as the absence of separated trash bins, waste banks, and long access to temporary disposal sites, as well as the lack of training for residents on how to utilize waste into something valuable.